Moral and political conceptions of human rights : implications for theory and practice / edited by Reidar Maliks, University of Oslo, Johan Karlsson Schaffer, Goteborgs Universitet, Sweden. - Maliks, Reidar; Schaffer, Johan Karlsson, 1976- (Cambridge University Press, 2017)
In recent years, political philosophers have debated whether human rights are a special class of moral rights we all possess simply by virtue of our common humanity and which are universal in time and space, or whether they are essentially modern political constructs defined by the role they play in an international legal-political practice that regulates the relationship between the governments of sovereign states and their citizens. This edited volume sets out to further this debate and move it ahead by rethinking some of its fundamental premises and by applying it to new and challenging domains, such as socio-economic rights, indigenous rights, the rights of immigrants and the human rights responsibilities of corporations. Beyond the philosophy of human rights, the book has a broader relevance by contributing to key themes in the methodology of political philosophy and by addressing urgent issues in contemporary global policy making.